PENGARUH ENDORSMENT DAN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO DI SILA - Fatima, Nurul; Ernawati, Sri (Lembaga Pengembangan Kinerja Dosen, 2023)
The formulation of the problem in this study is whether endorserment and equity affectthe purchasing decision of the oppo to sila. The purpose of this study is to determine the effect of endorserment and equity effect on the purchasing decision of oppo to sila smartphone. The hypothesis in this study is that endorserments and equity affect have a positve effect on consumer purchasing decisio on the oppo smartphone, the population is unknown. The sample is 100 people the data source comes from primary and secondary data. The results showed that the cofficient of determination R Square is 344. Simultaneous testing obtained Fcount (24.344) greater than Ftable (3,09) or (24.344 > 3.09) meaning that brand image and promotion together have a positive effect on consumer purchasing decisions. endorsments variable has a positive and significant effect on purchasing decisions consumers where the t-count value is 3.313 > the t-table value is 1.984. Partially the promotion variable has the most dominant influence on consumer purchasing decisions, where the t-count value is 3.313> t table 1.984